(untitled) (Research, Society and Development, 2022)
Physiotherapy works in several fields of the profession, one of which is to work with users with chronic non-communicable diseases, who have several respiratory and motor changes, from there palliative care aims to provide care to manage symptoms, psychosocial issues and spirituals in home care; The general objective of this study was to investigate the role of physical therapy in home care in patients under palliative care; The present study was an integrative review in which the Virtual Health Library (VHL) National Library of Medicine (Pubmed) and Online Scientific Electronic Library (Scielo) databases were used and the descriptors, "palliative care", “physiotherapy”, and “home treatment”, using the Boolean operators “AND” and “OR”. As inclusion criteria, articles published from 2017 to 2021 published in national and/or international databases in Portuguese, English and/or Spanish, and exclusion criteria that were duplicates and incomplete publications; 295 articles were found, of which 290 were excluded for not meeting the criteria. Only 5 were considered after reading the titles and abstracts. We can observe that the role of physiotherapy offers assistance in respiratory complications through bronchial hygiene techniques and maneuvers, lung reexpansion techniques and mechanical resources and in functionality with aerobic and resistance exercises; Physical therapy in home PCs offers more comfort and quality of life, promoting better social interaction and improved well-being, keeping you active to perform ADLs.